Branch-site occlusion sign predicts the embolic origin of acute ischemic stroke: a meta-analysis - Jiang, Xinzhao; Shi, Zongjie; Wang, Peng; Wang, Xu; Liu, Fang (Frontiers in Neurology, 2023)
Objective The study aimed to investigate whether branch-site occlusion (BSO) sign could predict the etiology of acute intracranial large artery occlusion (ILVO) and the stentriever (SR) response. Methods We systematically reviewed studies that evaluated the predictive role of BSO for the etiology of ILVO-AIS or EVT outcome between 1 January 2000 and 31 August 2022 from PubMed, Embase, and Web of Science. Results The sensitivity and specificity of BSO sign predicting etiology of ILVO-AIS were 0.87 (95% CI 0.81–0.91) and 0.64 (95% CI 0.33–0.87), respectively. The sensitivity and specificity of BSO sign predicting stentriever response were 0.84 (95% CI 0.63–0.94) and 0.61 (95% CI 0.18–0.92), respectively. Conclusion The BSO sign could be a valid and precise imaging marker to predict embolism caused ILVO-AIS and recanalization success by SR without rescue therapy.